The Global Food Security Crisis: Causes, Consequences and Solutions (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The global food security crisis has become one of the most pressing challenges of the 21st century, affecting billions of people worldwide. According to the United Nations, nearly 828 million people faced hunger in 2022, a figure exacerbated by conflicts, climate change, and economic disruptions. Ensuring food security—defined as access to sufficient, safe, and nutritious food for all—is crucial for global stability, health, and development. This article explores the causes and consequences of the crisis, examines potential solutions, and highlights the role of technology in addressing food insecurity.